CONCEPTUAL PRINCIPLES AND PRACTICAL ASPECTS OF FOREIGN TRADE SECURITY OF REGIONS IN MODERN CONDITIONS - Юлія Полякова; Валентина Куцик (Економіка та суспільство)
The article is dedicated to examining the conceptual foundations and practical aspects of external trade security of regions under modern conditions. It outlines general scientific approaches to defining the concept of “economic security of regions”. The article considers the national approach to ensuring economic security in Ukraine under crisis conditions and identifies the threats to economic security. It highlights the strengths, weaknesses, opportunities, and threats that the war poses to Ukraine’s foreign trade, allowing for the development of new approaches and adaptation to current challenges. It is determined that the European experience in protecting the field of foreign trade is extremely useful for Ukraine, particularly in the use of diplomatic tools for bilateral and multilateral trade cooperation. The article demonstrates that during the war, the nature of external trade security challenges in Ukrainian regions has shifted – from technological dependency to the reduction of export production and the destruction of export logistics. General trends in Ukraine's foreign trade are analyzed. The article presents an analysis of the volumes and shares of Ukrainian regions in foreign trade during the pre-war and wartime periods. It proves that the list of leading regions in foreign trade has undergone transformations, and that geographic location within the country, the practical use of transport and logistics infrastructure, and access to international markets have gained priority in terms of foreign trade security. It emphasizes that under the current conditions, when international trade is undergoing significant transformations due to new challenges, Ukraine’s foreign trade – both nationally and regionally – is primarily defined by its export capacity rather than economic rationality. It is substantiated that the development of trade relations with EU member states, based on European institutional and organizational support, will help minimize risks in ensuring regional external trade security in Ukraine.